2021
DOI: 10.4236/ojbm.2021.91021
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Mobile Banking Adoption in Uganda Using the Technology Acceptance Model (TAM2) and Perceived Risk

Abstract: The purpose of this study is to measure the adoption of mobile banking systems among the citizens of Uganda by analyzing the effect of perceived usefulness, perceived ease of use, and perceived risk on actual usage of mobile banking, with intention to use as a mediating variable. A closed-ended questionnaire was employed to be filled by Uganda citizens. A total of 275 questionnaires were sent out, among which only 245 were useable. A factor analysis test was run in order to establish the construct validity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Perceived risk in the banking sector connotes customers' apprehensions about safe transmission of user information, concerns about security of financial transactions and leakage of personal information (Cockrill, 2009;Lafraxo et al, 2018;Tam, 2012). Perceived risk has primarily been discussed in context to the Internet banking services and online shopping (Chauhan et al, 2019;Lafraxo et al, 2018;Milly et al, 2021). However, the theory of perceived risk has not been much emphasized in context to bank's automated teller machine (ATM) services and related transactions (Khan and Abdullah, 2019;Narteh, 2015).…”
Section: Moderating Effects Of Perceived Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…Perceived risk in the banking sector connotes customers' apprehensions about safe transmission of user information, concerns about security of financial transactions and leakage of personal information (Cockrill, 2009;Lafraxo et al, 2018;Tam, 2012). Perceived risk has primarily been discussed in context to the Internet banking services and online shopping (Chauhan et al, 2019;Lafraxo et al, 2018;Milly et al, 2021). However, the theory of perceived risk has not been much emphasized in context to bank's automated teller machine (ATM) services and related transactions (Khan and Abdullah, 2019;Narteh, 2015).…”
Section: Moderating Effects Of Perceived Riskmentioning
confidence: 99%
“…Perceived risk is defined as the perception of consumers regarding uncertainty and adverse consequences (Jayashankar et al , 2018; Jaradat et al , 2018). It represents individuals' viewpoint and might vary depending on his/her taste, judgment and experience (Mutahar et al , 2018; Milly et al , 2021; Ramos et al , 2018). The conceptualization of perceived risk asserts that certain consumer choices may lead to unforeseeable outcomes, and these outcomes might be displeasing (Mutahar et al , 2018; Ramos et al , 2018).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Ease of usage refers to the degree to which individuals consider a technology easy to use and are drawn to use it to solve job tasks. Applications of TAM2 have shown success in fields including education [39], health [6], and finance [40]. Even with the creation of new models serving similar functions, TAM 1 and TAM 2 continue to be employed in current studies as useful models [27].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Meanwhile, Nguyen and Huynh (2018) found that perceived risk had a negative but not statistically significant effect on trust. According to Milly et al (2021) research, an increase in perceived risk reduces the likelihood of continuing to utilize mobile banking. These findings are backed up by studies by Park et al (2019), Khan et al (2020), andObaid (2021), which found that perceived risk had a negative and substantial impact on continuing usage intention.…”
Section: Perceived Riskmentioning
confidence: 99%